Comparative Analysis of Reverse Martingale And Cumulative Win Strategies Using Ichimoku Kinko Hyo Indicator - Wendy, Vincent; Sunardi Oetama, Raymond (International Journal of Science, Technology & Management, 2023)
Given the dearth of prior research on the practical implementation of money management strategies in the foreign exchange market, making it arduous to ascertain profitable money management comparisons, this study places its focus on the amalgamation of money management strategies and technical indicators. The research specifically explores the utilization of two money management strategies, namely reverse martingale, and cumulative win strategy, in conjunction with Ichimoku Kinko Hyo serving as the chosen technical indicator. The primary aim of this research endeavor is to identify the most lucrative money management combination within a three-year timeframe. The study centers on the EURUSD currency pair, employing the H1 timeframe for analysis. The research methodology encompasses four essential stages: data collection, data processing, strategy testing, and result analysis. Subsequently, the acquired EURUSD data will undergo amalgamation utilizing the One-Way ANOVA method to determine the presence of statistically significant disparities between the two combinations. The outcomes of this investigation underscore the supremacy of the cumulative win strategy and Ichimoku Kinko Hyo combination, exhibiting a remarkable Return on Investment (ROI) surpassing alternative combinations, soaring to an impressive figure exceeding 2860%.